ACCUMULATION OF STRAIN AND RELEASE ON THE SUMATRA AREA BASED ON CONTINUOUS GPS OBSERVATION DATA SUMATRAN GPS ARRAY YEAR 2002-2008 - MAIYUDI (NIM: 251 12 010); pembimbing: Dr. Irwan Meilano, ST, M.Sc ; Dr. Ir. Dina A. Sarsito, , RIKO
The Sumatra island is located between two tectonic plates; the Indo-Australia Plate and the Eurasian plate. The intensity of the earthquakes is very large on the island because of this, especially along the western coastal area. On the 2002 to 2008 period, many large earthquakes that caused fatalities and large consequences have occured. These phenomenons shows that the studies of the deformation patterns of the Sumatra island is required. The studies are required for disaster mitigation plans in the future. The deformation patterns of the earthquakes can be observed with GPS (Global Positioning System) observations. The data that is being used for the Sumatra earthquakes is the Sumatran GPS Array. The software that is used for the processing of the Sumatran GPS array data of the Sumatra island is the Gamit 10.4. From the data processing, it can be concluded that there are displacements of the stations positions from the initial station coordinates. The displacements of the stations can be used if the outlier data has been erased. From the station displacement coordinates, we can obtain the displacement vectors of all of the stations before, during or after the earthquakes. From the displacement vector values, the values of the strain that occurs along the Sumatra island can be estimated. From the strain data, the accumulated value of strain and release from 2002 to 2008 can be obtained. The results of this study obtained Sumatra strain accumulation rate was 0,1 micro strain and the release of strain values uring the eartquake is approximately 0.65-7.83 micro strain. So Ir would take 6-78 years for the next earthquake